Cardiovascular Diseases: Exploring Epidemiology, Pathophysiology, Risk Factors, and Medicinal Plant‐Based Therapies: A Narrative Review - Nawfal Hasan Siam; Umme Halima Mithila; Sadia Alam Tisha; Hridoy Saha; Ayesha Binte Mahbub; Farhan Nizam; Johirul Islam; Noushin Tabasumma; Md. Mazharul Islam Chowdhury (Health Science Reports, 2026)
ABSTRACT Background and Aims Cardiovascular diseases (CVDs) remain the leading cause of global morbidity and mortality, encompassing coronary artery disease, hypertension, heart failure, and cerebrovascular disorders. The global burden of CVD continues to rise, driven by complex interactions among endothelial dysfunction, oxidative stress, inflammation, genetic predisposition, and lifestyle‐related risk factors. This review aims to provide a comprehensive overview of the epidemiology, pathophysiology, risk factors, and emerging therapeutic approaches for CVD, highlighting recent advances in precision medicine and phytotherapy. Methods A comprehensive literature search was conducted using PubMed, ScienceDirect, and Google Scholar databases. Keywords included “cardiovascular disease,” “Atherosclerosis,” “Pathophysiology,” “Risk Factors,” “Treatment,” “Hyperglycemia,” and “Hypertension.” Approximately 300 publications were initially identified. Following title, abstract, and full‐text screening, 156 relevant articles were selected for inclusion. About 85% of the reviewed literature was published between 2020 and 2025, while the remaining 15% originated from 2016 to 2019. Results The review demonstrates a substantial increase in the global burden of CVDs, with prevalence nearly doubling between 1990 and 2019 and mortality continuing to rise worldwide. Atherosclerosis emerged as the primary pathological basis of ischemic cardiovascular disorders, driven by endothelial dysfunction, oxidative stress, inflammatory cytokines, and vascular remodeling. Major modifiable risk factors include hypertension, smoking, diabetes, dyslipidemia, obesity, unhealthy diet, alcohol consumption, and physical inactivity, while age, sex, and genetic susceptibility contribute to disease risk. Emerging therapeutic strategies such as PCSK9 inhibitors, dual SGLT1/2 inhibitors, siRNA‐based therapies, CRISPR/Cas9 genome editing, and anti‐inflammatory biologics show promising clinical outcomes. Additionally, medicinal plants including Astragalus membranaceus , Citrus bergamia , Hibiscus sabdariffa , and Olea europaea exhibit cardioprotective effects. Conclusion CVD remains a significant global health challenge requiring multifaceted management strategies. The integration of conventional pharmacotherapy, precision medicine, gene‐based interventions, and evidence‐based phytotherapeutics offers promising opportunities to improve cardiovascular outcomes and reduce the growing global disease burden.